Compressed earth blocks for rural housing in seismic zones using bagasse fibers from sugarcane - Tello, Jose (2022)
The low resistance to compression and flexural of conventional earth techniques such as adobe in the occurrence of earthquakes causes the immediate collapse or failure of structures built with this material. These deficiencies are caused by the lack of stabilization and reinforcement processes of the block, which causes low mechanical performance in the face of seismic forces. The most common structures to collapse during earthquakes in developing countries such as Peru are the self-built adobe rural houses, being the most used in these areas due to the high housing deficit and the high demand for low-cost housing. One solution to this problem is the use of reinforced CEB in rural housing. In the present investigation some properties such as absorption, compressive strength and flexural strength are studied, the results indicate that the compressive strength and flexural strength increase when compared with an unstabilized earth block, however, the increase in absorption is proportional to the amount of fiber so it was used in small proportions less than 1% in the mixture.